"Czy pójdę do nieba?"-Prolegomena do badań nad duchowością dzieci - Grzywacz, Malgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
The subject of the article is the religious experience in the period of childhood.Beginning with the presence of children in the Bible, there follows an overview of different situations, opinions and concepts that explicate religious attitudes of children:for example towards death or serious illness. The author brings closer the cases of childrenwho had mystical experiences, like Ellen Organ (1903-1908) or Antonietta Meo(1930-1937).